Bildungsroman: Education Between the Indefinite and the Institutional - Vargas Arbeláez , Esther Juliana (2026)
This article was developed within the framework of the research project «The Problem of Formation: Updating a Fundamental Concept in Education and its Development in the Teaching of Philosophy», whose overarching objective is the revision of this fundamental concept in the field of education. As part of this project, this article focuses on analyzing the relationship between bildungsroman and the aims of formation. A documentary analysis method with a hermeneutic approach was used to contrast the concept of formation over one of the classic manifestations of this idea in the German context: the bildungsroman, specifically through the lens of Eschenbach's Parzival. The text unfolds as follows: first, a brief recap of the scope of the term bildungsroman and the elements of Parzival within this genre. Second, we address the issue of values and their cultural construction. Finally, we attend to the question of the scope of the title formation in bildungsroman, in relation to the purposes of these processes. This analysis leads to the clarification of elements that contribute to updating the concept of formation, considering its aims.